Peningkatan Kompetensi Guru PAI melalui Kegiatan Kultum Pagi di SMK PGRI 2 Kediri - Muhammad Akhsanul Muhtadin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Religious education is needed for every individual and as a school response to innovate such as cultural activities of teachers to students or students to students, one of which is with cult programs either from students to students or teachers to students, but in this study the cults were carried out by teachers to teachers. The focus of this research is how the preparation of teachers in delivering the morning cult, how to implement the morning cult and how the results of the morning cult activity on improving the competence of Islamic Religious Education (PAI) teachers at SMK PGRI 2 Kediri. This research is a type of qualitative research with a case study type using data collection methods; Observation, documentation and interview. The results of this study indicate that there is an increase in teacher competence, but the presenters do not yet have a detailed plan because they take into account the different readiness of each presenter, the implementation of the morning cult has been running smoothly even though there are still some obstacles from other teachers and the results of the cult activities morning cults can increase teacher competence, besides that morning cults can improve personal, social and professional skills of Islamic Religious Education teachers, but pedagogical competence does not increase significantly.